Analisis Buku Biologi SMA Kelas X Materi Kingdom Animalia Berdasarkan Literasi Sains Se-Kabupaten Deli Serdang - Fitriana Siregar; Hasruddin Hasruddin; Ely Djulia (Magister Pendidikan Biologi, Universitas Negeri Medan, 2016)
The aimed of this research was to know level of scientific literacy of Animalia Kingdom on senior high school biology book at grade X in Deliserdang. The method of this research was descriptive quantitative by analyzing 7 the Biology Books from different publisher for grade X on animalia Kingdom topic. Books was assessed by researcher. Researcher assessed Animalia Kingdom on Senior High School biology books at grade X in Deliserdang based of scale questioner Animalia Kingdom on Senior High School biology books grade X with science of the body of knowladge, science as a way of investigating, science as a way of thinking, and interaction science, technology, and society. Result of this research shown that persentage of thema science as a body of knowledge was 21,86%, persentage of science as a way of investigating was 15,27%, persentage of science as a way of thinking was 11,91%, and persentage of interaction science, technology, and society was 10,36%. It can be concluded that percentage of scientific literacy of Animalia Kingdom on Senior High School biology books at grade X in Deliserdang was 59,42% (not yet scientific literacy).